1990
DOI: 10.1126/science.2200125
|View full text |Cite
|
Sign up to set email alerts
|

Specific Tropism of HIV-1 for Microglial Cells in Primary Human Brain Cultures

Abstract: Human immunodeficiency virus (HIV) frequently causes neurological dysfunction and is abundantly expressed in the central nervous system (CNS) of acquired immunodeficiency syndrome (AIDS) patients with HIV encephalitis or myelopathy. The virus is found mostly in cells of the monocyte-macrophage lineage within the CNS, but the possibility of infection of other glial cells has been raised. Therefore, the effects of different HIV-1 and HIV-2 strains were studied in primary cultures of adult human brain containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
3
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(190 citation statements)
references
References 50 publications
7
179
3
1
Order By: Relevance
“…In vitro studies demonstrated that this brain-adapted virus replicated more ef®ciently in microglia and less ef®ciently in GSM than the parental virus. HIV tropism for microglia has also been demonstrated in vitro and has been shown to be determined by the same regions of the env that determine macrophage tropism (Sharpless et al, 1992;Watkins et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that this brain-adapted virus replicated more ef®ciently in microglia and less ef®ciently in GSM than the parental virus. HIV tropism for microglia has also been demonstrated in vitro and has been shown to be determined by the same regions of the env that determine macrophage tropism (Sharpless et al, 1992;Watkins et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…11 Infection of other cell types may also occur but remains controversial. While the infection of macrophages and microglia is a productive infection with formation and release of viral particles, 12 infection of astrocytes may result in viral latency and small amounts of virus are only released upon stimulation by cytokines. 13 Prominent dendritic pruning 14 , loss of synapses 15 and cell death 16,17 may occur in neurons.…”
Section: Pathologymentioning
confidence: 99%
“…As with HIV-1, the target for SIV infection in vivo and in vitro (Desrosiers et al, 1991;Lackner et al, 1991;Ringler et al, 1989;Wyand et al, 1988) is the CD4 molecule expressed on lymphocytes and monocyte/macrophages. Moreover, as with HIV-1, SIV isolated from encephalitic brains has been shown to be macrophage-tropic (Desrosiers et al, 1991;Simon et al, 1992Simon et al, , 1994Watkins et al, 1990;Wiley and Budka, 1991). Even when animals are infected with molecularly cloned lymphotropic virus (eg SIVmac239), approximately 30% of infected animals develop highly macrophage-competent variants (Desrosiers et al, 1991).…”
Section: Siv-infected Macaque Monkey Modelmentioning
confidence: 99%